Knowledge of strategic value discipline and its importance for fresh graduate: A qualitative investigation - Musallam Jaboob, Ali Said; Jaboob, Mohammed Said; Al Amri, Tariq Said (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Strategy formulation is an old practice that cuts through business and politics. The earlier human species have been regarded as the proprietors of strategy formulation as a part of existence. Therefore, the paper aims to evaluate strategy as a management discipline. In doing so, a qualitative research approach will be employed to analyze a variety of concepts in strategic management. The historical perspective of strategy formulation, as well as the importance of strategy in the modern-day business context, is discussed. Moreover, the emergence of strategy, strategic management, and planning in the business perspectives will be analyzed. Ultimately, this paper aims to demonstrate the importance of strategic management as a skill that would guide job-seeking graduates to work in organizations best suited for them.